Talent Management and Innovative Performance : The Role of HR - Maryam, Jalilzadeh (2013)
Due to the increasing competition among firms in the current business world, the demand of new products and services are on the rising trend. Therefore, companies should constantly enhance their innovative capabilities. This can be achieved through talent management which is one of the greatest challenges facing firms in this century. Companies should have the right policies, tools and strategies to attract, select and maintain talents. To further shed light on this issue, a case-study approach was employed to gather data on two firms with high degree of innovative performance. The HR managers along with other key personnel were interviewed to for an in-depth understanding of the methods they employed for attracting, selecting and retaining talents in their companies. The findings of the research indicate that there is a link between innovative performance and policies regarding talent management in the companies. Based on the findings of the study, some recommendations are provided for managers on their talent management policies.